Storied Rocks: Portals to Other Dimensions - Richard Stoffle; Kathleen Van Vlack; Alannah Bell; Bianca Eguino Uribe (Arts)
Storied Rocks (Tumpituxwinap) is a term of reference used by the Numic speaking tribal elders whom we have worked with for over 60 years on an estimated 200 ethnographic studies. Key to this analysis are the protocols for approaching, interacting, and using the places where Storied Rocks have been located. Concomitant with these traditional protocols are ones established to resolve the curiosity of non-Natives about why they are in a particular place and what they mean. This analysis shares the cultural understandings of tribal representatives who participate in these ethnographic studies. Studies used in the analysis were funded by U.S. federal agencies, supported by federally recognized Native American tribal governments, and composed with the cultural understandings shared and made public by tribally appointed elders to clarify the conundrums that are Storied Rocks.